Synthesis of {100} Facet Dominant Anatase TiO2 Nanobelts and the Origin of Facet‐Dependent Photoreactivity. Issue 46 (26th September 2014) - Pan, Feng; Wu, Kai; Li, Hexing; Xu, Guoqin; Chen, Wei
Abstract Sword‐like anatase TiO2 nanobelts exposed with 78 % clean {100} facets were synthesized and the facet‐dependent photoreactivity of anatase TiO2 was investigated. By quantitative comparison with the reference {001} facets, the {100} facets possessed about ten‐times higher active sites density than that on {001} facets, resulting in higher photoreaction efficiency. After the active sites density normalization, the {100} and {001} facets exhibited distinct wavelength‐dependent photocatalytic performance, attributed to the anisotropic electronic structures in TiO2 crystals.